Natural Killer (NK) Cell Education Differentially Influences HIV Antibody-Dependent NK Cell Activation and Antibody-Dependent Cellular Cytotoxicity - Bernard, Nicole F.; Kiani, Zahra; Tremblay-McLean, Alexandra; Kant, Sanket A.; Leeks, Christopher E.; Dupuy, Franck P. (Frontiers in Immunology, 2017)
Immunotherapy using broadly neutralizing antibodies endowed with Fc-mediated effector functions has been shown to be critical for protecting or controlling viral replication in animal models. In human, the RV144 Thai trial was the first trial to demonstrate a significant protection against HIV infection following vaccination. Analysis of the correlates of immune protection in this trial identified an association between the presence of antibody dependent cellular cytotoxicity (ADCC) mediated by immunoglobulin G (IgG) antibodies to HIV envelope V1/V2 loop structures and protection from infection, provided IgA antibodies with competing specificity were not present. Systems serology analyses implicated a broader range of antibody (Ab) dependent functions in protection from HIV infection, including but not limited to ADCC and antibody dependent NK cell activation (ADNKA) for secretion of IFN-γ and CCL4 and expression of the degranulation marker CD107a. The existence of such correlations in the absence of broadly neutralizing antibodies in the RV144 trial suggest that NK cells could be instrumental in protecting against HIV infection by limiting viral spread through Fc-mediated functions such as ADCC and the production of antiviral cytokines/chemokines. Beside the engagement of FcγRIIIa or CD16 by the Fc portion of anti-Env IgG1 and IgG3 Abs, NK cells are also able to directly kill infected cells and produce cytokines/chemokines in an Ab-independent manner. Responsiveness of NK cells depends on the integration of activating and inhibitory signals through NK receptors, which is determined by a process during their development known as education. NK education requires the engagement of inhibitory NK receptors by their HLA ligands to establish tolerance to self while allowing NK cells to respond to self cells altered by virus infection, transformation, stress and to allogeneic cells. Here, we review recent findings regarding the impact of inter-individual differences in NK cell education on Ab-dependent functions such as ADCC and ADNKA including what is known about the HIV envelope epitope specificity of ADCC competent Abs and the conformation of HIV envelope on target cells used for ADCC assays.